The Awareness of Space in the Experience of Listening - Esteve Roldán, Eva; Griffiths, John; Rodilla, Francisco (Brill, 2026)
By combining an evocative potential with practical application, this book presents studies that contribute to two of the most innovative approaches to early music in recent academic trends, namely, the exploration of the physical environment in which recovered repertoires were once performed, and how they may have been perceived by those who heard them. Current interest in the spatial context is not limited to identifying the specific places where musical performance took place, but extends to their topography, their acoustic conditions, and the sensory experience of the spectators for whom they were designed. The development and interconnection of these spatial, acoustic and sensory aspects is the main focus of the present volume. The rapid evolution and expansion of digital technologies in this field has helped to promote new explorations which, with increasing frequency, are presented in digital format and are able to become a modern-day auditory experience accessible to the general public.
La consciencia del espacio en la experiencia de la escucha
Keywords: early music; architectural acoustics; soundspace; senses